(untitled) (Bangladesh Rice Journal, 2026)
Studying genetic variability and key agro-morphological traits in rice is crucial for breeding because it identifies superior genotypes and reveals how traits are inherited, enabling breeders to select the best parents for developing new, high-yielding varieties. This process provides the essential data needed to plan effective crosses and make targeted improvements in rice crop. This study investigated the genetic variability and key agro-morphological traits of 33 rice genotypes to identify superior lines for future breeding programs. Understanding the genetic potential of these genotypes is crucial for developing high-yielding, resilient rice varieties. We evaluated ten quantitative traits, including days to 50% flowering, plant height, panicle length, and yield per hill. Data were analyzed using analysis of variance (ANOVA), genetic parameters, correlation coefficients, and multivariate techniques such as principal component analysis (PCA) and cluster analysis to determine genetic relationships and trait associations. Significant genetic variation (P≤0.05) was observed for all traits. The mean performance analysis identified genotypes with superior traits, such as IR146151-B-B-584-44-3(G-30) for the highest plant height (117.17 cm) and yield hill-1(31.71 gm), and IR146164-B-B-543-165-47(G-24) for the longest flag leaf (42.33 cm). High heritability and genetic advance were recorded for flag leaf length and spikelet fertility, indicating strong additive gene action. Yield hill-1 showed a significant positive correlation with the number of effective tillers hill-1(r=0.52), number of grains panicle-1 (r=0.72), and spikelet fertility (r=0.69). PCA revealed three principal components that explained 70.54% of the total variance. Cluster analysis grouped the genotypes into four distinct clusters, with the largest inter-cluster distance observed between clusters II and IV (5.45), highlighting their high genetic divergence. The study confirmed substantial genetic variability among the rice genotypes, which can be effectively utilized for crop improvement. The identified high-performing genotypes and traits with high heritability are promising for direct selection. Hybridization between genotypes from divergent clusters, particularly clusters II and IV, is recommended to create new genetic combinations and enhance yield potential in future rice breeding programs. Bangladesh Rice J.28(2): 55-69, 2024